Automated Regression Testing using Symbolic Execution - Barisas, D.; Milasius, T.; Bareisa, E. (Elektronika ir Elektrotechnika, 2011)
The aim of this paper is to describe a way to construct tests which validate that changes made during software evolution did not introduce regression faults. Developers usually run a new version of the program against the same set of tests. In order to achieve this goal, symbolic execution was used for test input generation and full structural code coverage. Moreover, the extension of symbolic execution was developed to increase the quality of tests. As a result, regression faults were detected in the program. The concept of the technique and an example model are presented. Ill. 7, bibl. 18 (in English; abstracts in English and Lithuanian). http://dx.doi.org/10.5755/j01.eee.112.6.457